Small RNA GcvB Regulates Oxidative Stress Response of Escherichia coli - Xian Ju; Xingxing Fang; Yunzhu Xiao; Bingyu Li; Ruoping Shi; Chaoliang Wei; Conghui You (Antioxidants, 2021)
Small non-translated regulatory RNAs control plenty of bacterial vital activities. The small RNA GcvB has been extensively studied, indicating the multifaceted roles of GcvB beyond amino acid metabolism. However, few reported GcvB-dependent regulation in minimal medium. Here, by applying a high-resolution RNA-seq assay, we compared the transcriptomes of a wild-type Escherichia coli K-12 strain and its gcvB deletion derivative grown in minimal medium and identified putative targets responding to GcvB, including flu, a determinant gene of auto-aggregation. The following molecular studies and the enhanced auto-aggregation ability of the gcvB knockout strain further substantiated the induced expression of these genes. Intriguingly, the reduced expression of OxyR (the oxidative stress regulator) in the gcvB knockout strain was identified to account for the increased expression of flu. Additionally, GcvB was characterized to up-regulate the expression of OxyR at the translational level. Accordingly, compared to the wild type, the GcvB deletion strain was more sensitive to oxidative stress and lost some its ability to eliminate endogenous reactive oxygen species. Taken together, we reveal that GcvB regulates oxidative stress response by up-regulating OxyR expression. Our findings provide an insight into the diversity of GcvB regulation and add an additional layer to the regulation of OxyR.